Pemikiran dan Perjuangan Ali Syari’ati - Mashadi Mashadi (Al-Ulum, 2011)
Ali Syariati is a world-class and brilliant scientist. He argued that Islam has a very principled nature and rational. Therefore, Islam must be considered as a school of ideology, not as a culture or collection of science. He displayed and introduced his teachings with what is termed as a liberation theology that combines re-interpretations of Islamic beliefs and socio-modern political thought. In addition, he also took an interest in the issue of humanism. He explained in detail and at length about this issue, both in the view of western leaders and intellectuals from the east. He said that today we face four different intellectual streams that states he represents humanism, namely western liberalism, Marxism, existentialism, and religion.